LOW PROTEIN DIET DURING PERIPUBERTAL PHASE PROGRAMS TO CARDIOVASCULAR DYSFUNCTION IN ADULT RATS - Rebeka Oliveira Ferreira, Anna; Vanusa Guedes Ribeiro, Maiara; Bernado Cornelio Coelho, Guilherme; Piovan, Silvano; Kian Guimarães Lopes, Gabriel; Ferreira Barbosa, Leticia; Cezar de Freitas Mathias, Paulo; Palma-Rigo, Kesia (Arquivos do Mudi, 2023)
Perinatal malnutrition has a devastation effect later in life. This study evaluated whether protein restriction in adolescent rats programs hypertension regarding cardiac dysfunction. CEUA approved the experimental protocol under nº 3353060421. 30-day-old Wistar male rats were fed a low protein diet (4%) for the next thirty days and subsequently fed a 20.5% normal protein diet for the next 60-days with normal diet (LP group). Control rats (NP group) were fed a normal protein diet throughout life. Cardiovascular system function was evaluated with 120-days-old. Statistical analyses were performed with T-Student test. LP animals displayed an inferior body mass and nose-tail length (P=0.0001; P=0.01) and also rising retroperitoneal fat (P=0.03). LP rats exhibited a higher in mean arterial blood pressure (p=0.05). In the echocardiogram, LP group showed an increased in the diameter (p=0.01, p=0.02), interventricular septum (p=0.040 e p=0.03) and the in posterior wall (p=0.01 e p=0.03) of the left ventricle in diastole and systole respectively. Protein restriction in peripubertal period leads to hypertension in adulthood, sustained by greater cardiac dysfunction.